Penerapan Model Pembelajaran Contextual Teaching and Learning (CTL) Berbantuan Media Audiovisual untuk Meningkatkan Kemampuan Pemahaman Konsep Matematika Siswa di SMP Swasta R.A Kartini Tebing Tinggi - Cronika Desranti Panjaitan; Pardomuan N.J.M. Sinambela (Departement of Mathematics Education, 2023)
The low ability to understand mathematical concepts of students in class VIII of Private Middle School R.A Kartini Tebing Tinggi is the background to this research problem. The purpose of this research is to improve students' understanding of mathematical concepts by applying the Contextual Teaching and Learning model assisted by audiovisual media. This type of research is classroom action research (PTK) which consists of 2 cycles. The place of this research is at RA Kartin Tebing Tinggi Private Middle School for the academic year 2022/2023. The subjects in this study were class VIII students, totaling 30 people. Methods of data collection using tests, questionnaires and observation sheets. The results obtained from the research show that there is an increase in the ability to understand concepts after using the Contextual Teaching and Learning model assisted by audiovisual media. The increase in conceptual understanding ability was seen from the average student score of 37.08 with a classical percentage of 3.3% before the action was given. After being given action in cycle I it increased to 67.5 with a classical percentage of 56.6% then increased again in cycle II to 81.67 with a classical percentage of 86.7%. From the results of the study it can be concluded that the application of the contextual teaching and learning model assisted by audiovisual media can improve the ability to understand the concepts of class VIII students of Private Middle School R.A Kartini Tebing Tinggi.